Concepto de hombre emprendedor: tendencias disciplinares (2021)
We explore the concept of the Entrepreneur Man (EM) that has emerged in two fields of knowledge, from the structural changes imposed by the new neoliberal social order in the last decades of the 20th century. In the field of Economics, EM has been associated with taking risks practices, innovating and detecting opportunities, which shows a tendency to incorporate notions/concepts/constructs/categories typically dealt by Psychology in general. In Organizational and Work Psychology, the EM concept was initially associated with personality traits, a notion that currently coexists with an approach that emphasizes the individual-context interaction, which tends to privilege notions / concepts / constructs / categories of a psychosocial nature. Finally, some questionsof contrast and analytical convergence of the EM are proposed in the twofields; as well as the importance of setting out the reciprocal influencebetween applied social sciences and their historical context, withoutdisregarding current tensions.